An organoruthenium complex overcomes ABCG2-mediated multidrug resistance via multiple mechanisms. Issue 26 (14th March 2019) - Zeng, Leli; Li, Jia; Zhang, Chen; Zhang, Yun-Kai; Zhang, Wei; Huang, Juanjuan; Ashby, Charles R.; Chen, Zhe-Sheng; Chao, Hui
Abstract : An organoruthenium complex, RuF, via multiple mechanisms, exhibited effective anticancer activity in vitro and in vivo for surmounting multidrug resistance mediated by the ABCG2 transporter. Abstract : Multidrug resistance mediated by the overexpression of ABC transporters is a major challenge in cancer chemotherapy. Here, we report the synthesis of an organoruthenium complex, RuF, that was designed to surmount multidrug resistance by combining ABCG2 inhibition and cancer cell cytotoxicity, yielding synergistic efficacy.